Cancer-associated fibroblasts in acute leukemia - Gu, Ling; Liao, Ping; Liu, Hanmin (Frontiers in Oncology, 2022)
Despite the prognosis of acute leukemia has been much improved, relapsed/refractory acute leukemia (R/R AL) remains challenging to treat. Recently, increasing evidences indicate that bone marrow microenvironment (BMM) plays a crucial role in leukemogenesis and therapeutic resistance, therefore, BMM-targeted strategies should be a potent protocol for R/R AL. Targeting cancer associated fibroblasts (CAFs) has got much attention in solid tumors and achieved some progress, since CAFs might act as an organizer in tumor microenvironment. Only recent 10 years, the roles of CAFs in BMM have obtained some attention. In spite of certain success in preclinical and clinical studies, the heterogeneity and plasticity make targeting CAFs a big challenge. Herein, we reviewed the heterogeneity and roles of CAFs in BMM, and highlighted the challenges and opportunities in CAFs-targeting therapy in acute leukemia.